Dear Leader : North Korea's Senior Propagandist Exposes Shocking Truths Behind the Regime - Jin-Sung, Jang; Translated By Shirley Lee (London Rider Books, 2014)
Contains new insights about North Korea which could only be revealed by someone working high up in the regime. This title is also the story of how a member of the inner circle of this enigmatic.
Include Map, Glossary and Index.
Keywords: Korea (North) -- Chang, Chin-sŏng -- Propaganda